Beginning Android programming with Android Studio - DiMarzio, J. F. (Indianapolis, New York : Wrox, A Wiley Brand, 2017)
"As the fastest-growing mobile platform today, the Android OS is a powerful and flexible platform for mobile devices and the new Android 5 release boasts significant new features and enhancements for both smartphone and tablet applications. This full-color resource takes a hands-on approach to teaching you how to create Android applications for the latest OS and the newest devices, including both smartphones and tablets." --Publisher annotation
1. Getting started with Android programming -- 2. Using Android studio for Android development -- 3. Activities, fragments, and intents -- 4. Getting to know the Android user interface -- 5. Designing your user interface with Views -- 5. Displaying pictures and menus with Views -- 6. Data persistence -- 7. Content providers -- 8. Messaging -- 9. Location-based services -- 10. Networking -- 11. Developing Android services -- 12. Answers to exercises
Includes index
Keywords: Android (Electronic resource); Application software -- Development; Mobile Devices; Smartphones -- Programming; Tablet computers -- Programming